Public procurement in Malaysia : objectives, principles, and transparency of e-procurement - Sitti Hasinah Abul Hassan (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
Public procurement is one of the key economic activities of the government and the main source for providing basic necessities for the citizens in a country. The public procurement activities are carried out by the government through government suppliers using public funds. The present study focuses on the government suppliers' perceptions of the public procurement activities in Malaysia. The aims of this study are (i) to explore the perceptions of the government suppliers of the importance of the public procurement objectives in Malaysia, (ii) to investigate the extent to which government suppliers adhere to the public procurement principles, and (iii) to examine the level of transparency of the e-procurement system in Malaysia. The current research was carried out using a quantitative research method by means of a questionnaire survey and content analysis. The questionnaire survey was used to achieve the first and second objectives of the research. Then, the descriptive analysis was used for the questionnaire survey. For the third objective, the Website Attribute Evaluation System (WAES) content analysis was used and analysed using frequency distribution. The total completed questionnaires were 107 all of which were usable. The results revealed that the most important public procurement objective is to ensure a continuous supply of material and services to meet the government needs from the best and reliable sources. However, the objective to expand the local industrial sector by means of the transfer of technology and expertise to suit the nation's needs, and the objective to promote alternative and multiple sourcing through supplier development according to the aspirations and vision of the government are not perceived as being important by the government suppliers. The findings also indicate a moderate level of adherence concerning Malaysia's public procurement principles, which consists of public accountability, transparency, open and fair competition, fair dealing, and value for money. The most adhered to principle is open and fair competition and the least adhered to principle is transparency. The findings from the WAES content analysis revealed that the overall transparency disclosure level of the ePerolehan system is 73.91 percent. The result implies a high level of transparency of the ePerolehan system in Malaysia. To ensure continuous improvement in the public procurement activities, the government may collaborate with academicians to further conduct comparative research from time to time to ensure that the information required for the users is being adequately disclosed. In conclusion, the research findings fill the gap in the studies on public procurement in Malaysia and provide information to researchers, and practitioners, particularly public procurement officers and the government of Malaysia.